Estudio de prefactibilidad para la instalación de una planta productora de licor crema de algarrobina con chocolate a base de pisco - Peña Pérez, Jorge Luis Antonio (2021)
The present project seeks to indicate the current market to determine the demand of the liquor algarrobin cream with chocolate based on Pisco, analyze the location factors for the installation of the plant, evaluate the size of the processing plant, the technical feasibility and evaluate the economical-financial viability of the project. For this reason, each chapter will detail the necessary factors to find these main and specific goals. The first chapter will show the scope of the project and the specific objectives. An explanation of the conceptual and referential framework of the proposed product as well. The second chapter will present the demand that the project will have. This demand is 58,820 bottles of the product developed. In addition, this chapter will include the general aspects of the market and the marketing strategy that will be used in the product. And the third chapter delves into the factors of location of the plant taking into account the variables, not only the micro but also the macro location for the installation of the production plant. Therefore, the selection chosen is San Juan de Lurigancho – Lima. The fourth chapter will define the relationships: size-market relationship, size-productive relationship, size-technology relationship and size-balance point. The best size is the size- technology relationship. And the fifth chapter will detail the product specifications and the technology required for its elaboration. A possible plant layout will be described, considering all safety recommendations and the production, as well. The sixth chapter will point out the type of organizational scheme including the administrative structure that the company will have. Finally, the seventh and eighth chapter will remark the budget including production costs, the required investment, and the analysis of an economical - financial evaluation in order to obtain necessary indicators for the project.